Broadband Polarization-Independent Edge Couplers With High Efficiency Based on SiN-Si Dual-Stage Structure - Yang Jiang; Zhewei Zhang; Peng Liu (IEEE Photonics Journal)
Silicon nitride (SiN) plays a critical role in silicon photonics because of its lower refractive index, low waveguide loss, broad operating bandwidth and compatibility with complementary metal oxide semiconductor (CMOS) fabrication process. Here, we propose a polarization-independent sub-wavelength grating (SWG) edge coupler with high efficiency based on SiN-Si dual-stage structure with a length of only 315.8 μm. Such a structure can be fabricated on 8-inch silicon photonics pilot lines and doesn't require special fabrication processes for making it suspended. We simulate the minimum TE/TM light coupling loss from a standard SMF-28 fiber to be 0.61 dB/0.95 dB with polarization dependent loss (PDL) less than 0.4 dB in the whole band between 1500 nm and 1600 nm.